Optimal cooperative strategy based on quantum bat for cognitive radio of energy harvesting - Hongyuan GAO; Yanan DU; Shibo ZHANG; Dandan LIU (Tongxin xuebao)
In order to reduce energy consumption and improve spectral efficiency of the cognitive relay wireless communication system in 5G network,an optimal cooperative transmission strategy of information and energy was designed for cognitive relay radio with wireless energy harvesting.For the proposed optimal cooperative strategy,the maximal throughput formula and outage probability of secondary user were deduced.In order to resolve the derived maximum throughput equation,a quantum bat algorithm which was based on the optimization mechanism of quantum computing and bat algorithm was designed to solve the deduced equation,and the optimal cooperative transmission scheme for information and energy could be obtained.Simulation results show that the proposed optimal cooperative strategy not only can meet the information transfer demand of primary user,but also can realize the energy self-supply of the secondary user system and improve the communication quality of the secondary user.The proposed optimal cooperative strategy has a better performance than the cooperative strategy of existing cognitive relay radio for different simulation scenarios.